WATER POLITICS AND POPULIST GOVERNANCE IN MALAYSIA: A CASE STUDY OF MUHAMMAD SANUSI MD NOR ADMINISTRATION IN KEDAH, 2020-2024: (Politik Air dan Pemerintahan Populis di Malaysia: Kajian Kes Pentadbiran Muhammad Sanusi Md Nor di Kedah, 2020–2024) (Applied History Journal of Merong Mahawangsa, 2025)
In this article, I examine the intersection between water governance and populist political strategies in Malaysia by focusing on the administration of Muhammad Sanusi Md Nor, the Chief Minister of Kedah from 2020 to 2024. The study investigates how the issue of inter-state water disputesparticularly Kedah’s demand for payment from Penang for raw water from Sungai Muda has been politicised and deployed as a populist narrative to consolidate political legitimacy. Drawing on the hydro-hegemony framework and theories of resource nationalism, I argue that Sanusi’s administration strategically framed water not merely as a resource, but as a symbol of state sovereignty and economic justice. Through qualitative content analysis of public speeches, policy documents, and media coverage between 2020 and 2024, this study reveals how water politics in Kedah reflect deeper tensions in Malaysia’s federal-state dynamics and the absence of a coherent legal framework for transboundary water governance. I demonstrate that the water discourse under Sanusi’s leadership illustrates a distinctive form of populist governance where rhetorical appeals to state rights, economic victimhood, and resource control are mobilised to assert autonomy within a fragmented federal structure. The findings contribute to broader discussions on environmental populism, subnational resource disputes, and the politicisation of infrastructure in emerging democracies. This study also highlights the urgent need for a comprehensive federal policy on water-sharing agreements to prevent political exploitation of vital resources.